HIGH SCHOOL STUDENTS’ CRITICAL THINKING ABILITY - Agustin, Puput Dwi; Prayitno, Lydia Lia (Program Studi Pendidikan Matematika FKIP Universitas Pattimura, 2023)
Problem solving is an important skill, and making decisions about the basis of critical thinking skills. This study is a descriptive qualitative study to describe the critical thinking of 8th grade public junior high school students in the suburbs of Surabaya, East Java in solving TVLS problems. Fifteen junior high school students contributed to the study and were given questionnaires to get three subjects with different critical thinking abilities. Furthermore, each subject was requested to solve TVLS word problems and then interviewed. The instruments used in this study were a critical thinking questionnaire (CTAT), TVLS word problems, semi-structured interview guidelines. The data was analyzed based on indicators that combined the stages of Polya's problem solving and critical thinking. The data were analyzed using critical thinking indicators that have been determined by the authors and the results obtained showed that (1) uncritical and low critical subjects were unable to complete the critical thinking indicators at each stage of problem solving; (2) medium critical, critical, and highly critical subjects were able to complete the critical thinking indicators at each stage of problem solving. For this reason, it is advised that teachers teach their students to think critically in solving problems in every learning process